2013
DOI: 10.5533/dst-2177-8264-201325102
|View full text |Cite
|
Sign up to set email alerts
|

EpidEmiological analysis of congEnital syphilis in thE statE of cEará, Brazil

Abstract: Introduction: congenital syphilis is a systemic infectious disease of chronic evolution caused by the Treponema pallidum bacterium dissemination to the fetus through the placenta of infected pregnant women untreated or treated improperly, occurring at any stage of pregnancy or clinical stage of the disease. Objective: epidemiological analysis of congenital syphilis in the State of Ceará from 2007 to 2010. Methods: documentary study conducted in March, 2013, through the database available at the Center for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
0
4
0
1
Order By: Relevance
“…Interestingly, it was found that despite the predominance of prenatal care in 70+% of the CS cases investigated herein, signi cantly high numbers of cases of CS were nonetheless reported throughout the country. While prenatal care is becoming more commonplace in Brazil, this rate still remains below the recommendations established by the Ministry of Health, which advocate that prenatal care must be properly provided to all pregnant women [28]. It is known that the noti cation rate of syphilis is considered to be an important indicator of accessibility and prenatal care quality [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it was found that despite the predominance of prenatal care in 70+% of the CS cases investigated herein, signi cantly high numbers of cases of CS were nonetheless reported throughout the country. While prenatal care is becoming more commonplace in Brazil, this rate still remains below the recommendations established by the Ministry of Health, which advocate that prenatal care must be properly provided to all pregnant women [28]. It is known that the noti cation rate of syphilis is considered to be an important indicator of accessibility and prenatal care quality [23].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, actions designed to improve health care access for pregnant women have performed poorly in terms of CS prevention [21]. One of the main purposes of prenatal care is to assist women in a quali ed and humanized way beginning in the early stages of pregnancy, adopting early screening procedures coupled with timely interventions [28]. Early diagnosis and treatment of SiP, ideally before the 20 th week of pregnancy, can reduce CS-related cases, such as miscarriages, stillbirths, and infant deaths [29].…”
Section: Discussionmentioning
confidence: 99%
“…An epidemiological analysis on congenital syphilis was carried out by Catunda et al (2013) [25] in the state of Ceará (northeast of Brazil), from 2007 to 2010. Among 1132 women, 71.78%, of their children had congenital syphilis infection, underwent prenatal care and access to diagnostic tests, and occurred only during delivery or curettage.…”
Section: Discussionmentioning
confidence: 99%
“…Among 1132 women, 71.78%, of their children had congenital syphilis infection, underwent prenatal care and access to diagnostic tests, and occurred only during delivery or curettage. Most of its partners held no treatment and the children were diagnosed in the recent form of the disease, i.e., in the maternity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Em uma série histórica do Ceará de 2013 observou-se aumento do número de consultas de pré-natal ao longo do tempo, mas apenas 41,3% foram diagnosticadas ainda no pré-natal e 69,5% dos parceiros não receberam tratamento. Houve também aumento do número de casos durante a curetagem ou assistência ao recém-nascido em mais de 50% dos casos 16 .…”
Section: Fatores De Riscounclassified